Complement in Kidney Transplantation - Cernoch, Marek; Viklicky, Ondrej (Frontiers in medicine, 2017)
The complement system is considered to be an important part of innate immune system with a significant role in inflammation processes. The activation can occur through classical, alternative, or lectin pathway, resulting in the creation of anaphylatoxins C3a and C5a, possessing a vast spectrum of immune functions, and the assembly of terminal complement cascade, capable of direct cell lysis. The activation processes are tightly regulated; inappropriate activation of the complement cascade plays a significant role in many renal diseases including organ transplantation. Moreover, complement cascade is activated during ischemia/reperfusion injury processes and influences delayed graft function of kidney allografts. Interestingly, complement system has been found to play a role in both acute cellular and antibody-mediated rejections and thrombotic microangiopathy. Therefore, complement system may represent an interesting therapeutical target in kidney transplant pathologies.
Keywords: kidney transplantation; antibody-mediated rejection; anticomplement therapy; ischemia/reperfusion injury; complement